Adherence Rating Scale for Cognitive Processing Therapy – Cognitive Only: Analysis of Psychometric Properties. Issue 6 (21st February 2017) - Dittmann, Clara; Müller-Engelmann, Meike; Resick, Patricia A.; Gutermann, Jana; Stangier, Ulrich; Priebe, Kathlen; Fydrich, Thomas; Ludäscher, Petra; Herzog, Julia; Steil, Regina
Abstract : Background : The assessment of therapeutic adherence is essential for accurately interpreting treatment outcomes in psychotherapy research. However, such assessments are often neglected.Aims : To fill this gap, we aimed to develop and test a scale that assessed therapeutic adherence to Cognitive Processing Therapy – Cognitive Only (CPT), which was adapted for a treatment study targeting patients with post-traumatic stress disorder and co-occurring borderline personality symptoms.Method : Two independent, trained raters assessed 30 randomly selected treatment sessions involving seven therapists and eight patients who were treated in a multicentre randomized controlled trial.Results : The inter-rater reliability for all items and the total score yielded good to excellent results (intraclass correlation coefficient [ICC] = 0.70 to 1.00). Cronbach's α was .56 for the adherence scale. Regarding content validity, three experts confirmed the relevance and appropriateness of each item.Conclusion : The adherence rating scale for the adapted version of CPT is a reliable instrument that can be helpful for interpreting treatment effects, analysing possible relationships between therapeutic adherence and treatment outcomes and teaching therapeutic skills.